A systematic review of the effectiveness of mass media campaigns for the management of low back pain. Issue 24 (20th November 2021) - Suman, Arnela; Armijo-Olivo, Susan; Deshpande, Sameer; Marietta-Vasquez, Janelle; Dennett, Liz; Miciak, Maxi; Reneman, Michiel; Werner, Erik L.; Straube, Sebastian; Buchbinder, Rachelle; Gross, Douglas P.
Abstract: Purpose: To synthesize evidence on the effectiveness of mass media campaigns for the management of LBP on beliefs of the general public and health care providers, LBP-related disability, health utilization, and LBP clinical outcomes. Materials and Methods: Five electronic databases were searched from inception to December 17, 2019. Any studies evaluating the effectiveness of mass media campaigns for LBP were eligible. Primary outcome was general public LBP beliefs, while secondary outcomes included health care provider beliefs as well as LBP-related disability, health utilization, and clinical outcomes. Results: The search resulted in 4, 164 unique records, of which 18 studies were included. These 18 studies predominantly used quasi-experimental methods to evaluate seven LBP mass media campaigns conducted in seven countries. All studies evaluating LBP beliefs in the general public detected positive effects. Health care provider beliefs also consistently improved. Results for behavioural outcomes (disability behaviour and health utilization) were mixed and appeared dependent on campaign characteristics and local context. Conclusions: Mass media campaigns for LBP appear effective for improving beliefs of the general public and health care providers. Registration: Prospero CRD42018116797 IMPLICATIONS FOR REHABILITATION: Mass media campaigns about low back pain (LBP) appear effective for improving beliefs of the general public and health care providers, aligning beliefs with current evidence and self-management principles. Rehabilitation professionals should be aware of and seek to support public education initiatives in their communities related to LBP and other disabling health conditions. Rehabilitation professionals can highlight and reinforce campaign messages when providing education and reassurance to individual patients. Several campaign resources (i.e., posters, pamphlets, electronic resources, etc.) are available for rehabilitation professionals to use in their efforts to reduce disability related to LBP.